Ultrasound-guided central venous catheter placement in the emergency department: Experience in a hospital in Bogotá, Colombia (2018)
Introduction: The use of central venous catheters (CVCs) in the emergency room (ER) is a valuable tool for the comprehensive management of critically ill patients; however, the positioning of these devices is not free of complications. Currently, the use of ultrasound is considered a useful and safe tool to carry out these procedures, but in Colombia, the number of emergency departments providing this tool is scarce and there is no literature describing the experience in our country. Objective: The objective of this study was to describe the experience regarding placement of ultrasound-guided CVCs by emergency physicians in an institution in Bogotá, as well as the associated complications. Materials and methods: This is a descriptive cross-sectional retrospective study. Medical records of 471 patients requiring insertion of CVCs in the resuscitation area from January 2014 to December 2014 were reviewed. Insertion site and complications are described. Results: For 471 total cases, the average age of patients was 68.6 years, the most frequent diagnosis was sepsis (30.7%), the preferred route of insertion was the right internal jugular vein, and insertion was successful at the first attempt in 85.9% of patients. Pneumothorax was the most common complication (1.2%), followed by extensive hematoma and infection. Conclusion: Insertion of ultrasound-guided CVCs by emergency physicians is a safe procedure that involves complications similar to those reported in the literature; it is necessary to expand the use of ultrasound-guided CVCs in ERs. © 2018 Devia Jaramillo et al.